2006
DOI: 10.1007/s00000-006-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Special features of the deformation-induced order-disorder phase transition and its modeling

Abstract: Methods of x-ray diffractometry are used to investigate the influence of plastic deformation on the state of the longrange order in alloys with the L1 2 , L1 2 (М), and L1 2 (MM) superstructure. It is demonstrated that the heterogeneous order-disorder phase transition accompanied by intensive accumulation of antiphase boundaries occurs under plastic deformation. The antiphase boundaries play an important role in the destruction of long-range order. Based on the available experimental results, a model of destru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Figure 3 presents results of the XRD study. This assumption is in line with the XRD results presented by Starenchenko and Starenchenko, [34] indicating on a presence of deformation-induced long to-short range order phase transition from the L1 2 to lower symmetry structures. The cold rolling leads to prominent changes of a relative intensity, a position and a width of diffraction lines.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 3 presents results of the XRD study. This assumption is in line with the XRD results presented by Starenchenko and Starenchenko, [34] indicating on a presence of deformation-induced long to-short range order phase transition from the L1 2 to lower symmetry structures. The cold rolling leads to prominent changes of a relative intensity, a position and a width of diffraction lines.…”
Section: Resultssupporting
confidence: 91%
“…The aforementioned authors concluded that the maintenance of the LRO 110/220 value during the cold-rolling of the Ni 3 Al-based alloy must be an effect of reordering (rather than complete disordering). This assumption is in line with the XRD results presented by Starenchenko and Starenchenko, [34] indicating on a presence of deformation-induced long to-short range order phase transition from the L1 2 to lower symmetry structures. Nevertheless, it is reasonable to assume that the difference in the behavior of the (110)/(220) line pair is also related to textural changes upon cold rolling.…”
Section: Resultssupporting
confidence: 91%
“…However, it is well known that this technique can induce disordering in ordered materials. Atomic disordering can subsequently induced phase transformations in intermetallic compounds [5][6][7][8]. On the other hand, MA process has also been used to produce Al-Cu-Fe icosahedral quasicrystals starting from elemental powders [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Origins of the yield strength anisotropy in the partially recrystallized Ni 3 Al alloy may be attributed to following structural features: an inhomogeneity of mechanical properties: deformed, strain hardened grains are surrounded by necklaces of recrystallized, "soft" grains; an morphological structure inhomogeneity: deformed, elongated grains are located beside of recrystallized, equiaxed ones; an inhomogeneity of long range order: according to works by Rentenberger and Karnthaler [47] and by Starachenko and Starachenko [48] in some L1 2 ordered phases (e.g. Cu 3 Al or Ni 3 Al) the restoration of long range order upon a post-deformation annealing takes place locally (in sites of local strain concentrations).…”
Section: Static Tensile Testsmentioning
confidence: 97%